A review of controlling strategies of the ignition timing and combustion phase in homogeneous charge compression ignition (HCCI) engine. (1st February 2021) - Duan, Xiongbo; Lai, Ming-Chia; Jansons, Marcis; Guo, Genmiao; Liu, Jingping
Highlights: The merits and demerits of the different combustion modes are comprehensively discussed. Effective strategies are systematically reviewed to overcome the limitations of the HCCI engine. Ignition timing and combustion phase are still the main challenges for the HCCI engine application. Combination strategies are proposed to optimize the auto-ignition timing and combustion phase. Abstract: Generally, the homogeneous charge compression ignition (HCCI) engine presents superior fuel economy and ultra-low NOx and particle matter emissions compared with the traditional combustion engine. However, the HCCI engine is essentially decoupled from the spark plug and fuel injection. That means the HCCI engine has no direct control mechanism for the auto-ignition timing and subsequent combustion phase. Without effective strategies to control the auto-ignition timing on time according to the operating conditions, the HCCI engine will be limited in a small operation range due to the cold start problem, high pressure rate and combustion noise, and even knocking combustion at the high-load. Generally, the properties of physical–chemical kinetics of fuels, as well as the mixture temperature spatial and temporal changing histories in the cylinder, strongly determine the ignition timing and affect the combustion phase in HCCI engine. Some effective techniques and controlling strategies, such as fuel management, homogeneous charge preparation, exhaust gas recirculation, etc. are widely used in the HCCI engine. These techniques and controlling strategies are used solely or conjunctively with each other to control the compressed gas temperature, pressure and mixture distribution in the cylinder at the end of the compression stroke so that the charge mixture could be auto-ignited at the desired crank angle, and thereby obtaining optimal combustion phase and heat release rate on a wide operation range for the HCCI engine. Thus, this paper comprehensively reviews different effective techniques and controlling strategies used in the HCCI engine, and also summarizes in the tables.